Compendium of Key Human Rights Documents of the African Union (Seventh Edition) - Heyns, Christof; Killander, Magnus (Pretoria University Law Press (PULP), 2022)
This is the seventh edition of the Compendium of key human rights documents of the African Union updated to June 2022. It is the first edition published since the untimely passing of Prof Christof Heyns who approached me many years ago with the idea for this Compendium. The Compendium was first published in 2005 and thereafter regularly updated. This compendium contains documents on human rights adopted under the auspices of the African Union (AU) and its predecessor, the Organization of African Unity (OAU), including documents adopted by the African Commission on Human and Peoples' Rights, the African Court on Human and Peoples' Rights and the African Committee on the Rights and Welfare of the Child. Since the sixth edition of this Compendium was published in 2016 there has been several normative developments but due to space reasons only a small number of the key new documents have been included in this edition. Due to space constraints only extracts are reprinted of many of the documents. This compendium is by no means comprehensive but includes some key documents of relevance for students of the African human rights system and others interested in its functioning. Extracts from documents related to the New Partnership for Africa's Development (NEPAD) and the African Peer Review Mechanism (APRM) reprinted in previous editions of this compendium have been left out of this edition. For comprehensive coverage of human rights law in Africa, see www.chr.up.ac.za and the web sites listed at the end of this compendium. The assistance of Frans Viljoen, Trésor Makunya, Clement Agyemang, Omotunde Enigbokan and Lizette Hermann in preparing this edition of the compendium and the financial support of the Norwegian government for its printing is gratefully acknowledged.